5-alpha-reductase deficiency: a case report - Diana Mettadewi Jong; Aman B Pulungan; Bambang Tridjaja AAP; Jose RL Batubara (Indonesian Pediatric Society, 2003)
The condition of 5-alpha-reductase type 2deficiency (5-ARD) is an inherited disorderresulting in the inability to converttestosterone to dihydrotestosterone(DHT).This disorder was previously termed asfamilial incomplete male pseudohermaphroditism type2, pseudovaginal perineoscrotal hypospadias.Clinical manifestation of 5-ARD is limited to malegenetic. The affected males are usually identifiedas female in childhood but undergo striking virilizationat puberty.While overall incidence for various countries arenot established, increased incidence is reported in theDominican Republic, some highland tribes in NewGuinea, Lebanon and Turkey. This was the firstdocumented case in Cipto Mangunkusumo (CM)Hospital.